Art and landscape history: British artists in nineteenth-century Val d'Aosta (north-west Italy). (3rd July 2018) - Piana, Pietro; Watkins, Charles; Balzaretti, Ross
ABSTRACT: This paper explores the value of landscape and topographical art for understanding contemporary landscapes of the Val d'Aosta, northwest Italy. The region became very popular with British tourists in the early nineteenth century and several amateur and professional artists depicted its landscapes. The paper focuses on the case study of Saint-Pierre, its castle and the surrounding landscapes, examining views by amateur artists like Henrietta Fortescue and professionals such as John Brett. The examination of art, alongside written accounts, historical cartography and field data, provides insights into the landscape history of the Val d'Aosta. The analysis of the artists' representations raises questions of landscape identity and characterisation and provides evidence for subtle changes in local landuse practices which have had a significant impact on land use change. We suggest that this artistic heritage should be recognised as a source to help improve sustainable tourism in the area and to assist in the development of current land management policies.